BAYI BERAT LAHIR RENDAH BERISIKO UNTUK TERJADI ASFIKSIA NEONATORUM - Purwaningsih, Sri; Susanti, Dwi (Universitas Jenderal Achmad Yani Yogyakarta, 2013)
Background : Based on WHO (World health Organization), amount 3,6 million (3%) from 120 million baby birth befound neonatorum asfiction almost 90%, baby mortality happen in developing country. Main factor of neonatal mortality are neonatorum asfiction (27%) and low Birth Weight. Purpose : For know relation low birth weight with neonatorum asfiction. Methode : Analitik survey with observasional crossectional design place of riset in perinatologi ward RSUD Wates. Subject of riset is all baby birth in perinatologi ward year 2 on with inclusion and exclusion standart. Data seek by medical record with secondary data used analysis kendall,s tau technique and correlation coefision. Result : Amount 326 subject of riset, almost baby birth is median birth weight 217 baby (67%). Almost asfiction in baby birth with apgar score 4 ? 6 is 159 baby (49%). There was relationship low birth weight with neonatorum asfiction with p value 0,013. Conclusion : There was relationship low birth weight with neonatorum asfiction is very low. Keywords : Low birth weight, neonatorum asfiction.